IMPROVEMENT OF LEARNING ACTIVITIES IN SCIENCE LEARNING THE FOURTH GRADE STUDENTS OF STATE ELEMENTARY SCHOOL THROUGH THE MODEL OF PREDICT OBSERVE EXPLAIN (POE) - Bety Permata Ningtyas; Hasan Mahfud; Karsono Karsono (Universitas Sebelas Maret, 2018)
This classroom action research was aimed to increase learning activity, improve student’s cooperation in learning and self-confidence in students. The object of this research are students class IV SD Negeri Pajang II No.171 Surakarta Academic Year 2017/2018 by applying the model of Predict Observe Explain (POE) in science learning. This research was conducted of three cycles and each cycle consists of four stages of planning, action, observation, and reflection. Data collection techniques are using tests, observations, interviews and documentation. Data validity technique are using content validity and triangulation of technique. Data analysis technique is interactive analysis model which consists of four components, namely data provision, data reduction, data presentation, and conclusion. The result of the research shows that model Predict Observe Explain (POE) can improve learning activities on student class IV of SD Negeri Pajang II No.171 Surakarta in academic year 2017/2018.